Respiratory allergy to moth: the importance of sensitization to Bombyx mori in children with asthma and rhinitis - Laura M.L. Araujo; Nelson A. Rosário Filho; Carlos A. Riedi (Brazilian Society of Pediatrics, 2014)
Objective: this study aimed to prepare a silkworm moth (Bombyx mori) antigenic extract and to perform skin prick tests with this extract in patients with allergic respiratory diseases; to evaluate serum specific immunoglobulin E (IgE) to Bombyx mori using ImmunoCAP® system and to compare the frequency of positivity between the two methods and with clinical data. Methods: this was a cross-sectional study with 99 children and adolescents diagnosed with asthma and/or allergic rhinitis, who had skin reactivity to at least one of the six aeroallergens tested. Clinical data were evaluated, skin prick tests with Bombyx mori in-house extract, and total and specific IgE analysis using ImmunoCAP® were performed. Results: the frequency of Bombyx mori specific IgE was found to be 52.5% and 60% using the skin prick test and ImmunoCAP®, respectively. An association between a positive skin test for Bombyx mori and the presence of allergic rhinitis, atopic dermatitis, and urticaria was observed, but the same was not true for asthma or allergic conjunctivitis. There was no relation with the severity of asthma or rhinitis symptoms. Conclusions: a high frequency of sensitization to Bombyx mori was observed in a selected population of patients with respiratory allergic diseases in the city of Curitiba, state of Paraná, Brazil. The extract prepared from the wings of this moth species is effective in demonstrating this sensitivity.